Curated eLearning in South Africa: A user burgeoning perspective - Goosen, Wynand (American Journal of Online and Distance Learning, 2023)
Purpose: This investigates the role of curation as an agile way of improving learner experience in eLearning. The current eLearning systems in South Africa often fail to provide effective learning experiences due to their one-size-fits-all approach, such as the assumption that eLearning can replace the educator's role. The absence of a "support process" for eLearning hampers effective learning. The current Digital Eco System focuses on eLearning with limited regard for learner contexts. Methodology: The International Youth Foundation (IYF) "curated" a program consisting of a Google Certificate, Critical Thinking, and Life Skills called "Skills for Success" (S4S). The curated program was completed by 500 learners. A survey of the learners was conducted to interpret user experience. A literature review, including journals, conferences, books, and websites, supports the research survey. The researcher's experience and observations are also documented. Concepts and Categories are identified from where "themes" are identified. Findings are made using grounded theory. Findings: The grounded theory process indicates that the learning landscape requires a "Curated Learning System". Process curation includes WhatsApp, Email, Telephonic Support, Zoom, Teams, and SMS, whilst content curation includes Critical-Thinking, Passport-to-Success and a Google Certificate, all delivered in one program called "Skills for Life". The "curation" of eLearning consists of "process" as well as "content" for more effective programs. Traditional support from facilitators is required in a non-traditional format. The research is confined to the "curation" of learning that is delivered online. Quality of Learner Management and online eLearning systems are excluded. Recommendations: From the themes, the research supports the role of content and process-curated learning, a need for more agility in eLearning delivery, and the importance of having a Home Space, a Work Space, and a "Third Space" where effective learning can occur. The research also shows how technology drives the development of a Digital Framework for delivering effective learning programs and the evolution of Homo Digitalis.